CRISPR/Cas9-Mediated Development of Potato Varieties with Long-Term Cold Storage and Bruising Resistance - Massa, Gabriela Alejandra; Decima Oneto, Cecilia Andrea; Gonzalez, Matías Nicolás; Poulsen Hornum, Anabela; Arizmendi, Ailín; Sucar, Sofia; Divito, Silvina Beatriz; Feingold, Sergio Enrique (MDPI, 2025)
Enzymatic browning and cold-induced sweetening (CIS) affect the post-harvest quality of potato tubers. Browning is caused by polyphenol oxidase 2 (PPO2), which is activated by mechanical damage during harvest and storage. CIS occurs when vacuolar invertase converts sucrose into reducing sugars, which react with amino acids during frying, forming brown pigments and acrylamide. While cold storage prevents sprouting and disease, it also increases vacuolar invertase expression, leading to quality loss. Using CRISPR/Cas9, we developed gene-edited potato lines with improved resistance to browning and CIS. Line 6A (cv. Atlantic) and E03-3 (cv. Spunta) exhibited complete vacuolar invertase (InvVac) knockout, maintaining chip quality for at least 60 days at 4 °C. Line 6A, renamed PIRU INTA, was tested in field trials and preserved frying quality for up to 90 days under cold storage. PIRU INTA is currently undergoing registration as a new variety. Additionally, lines E04-5B and E03-3 (cv. Spunta) showed partial PPO2 gene edits, reducing enzymatic browning by 80% and 40%, respectively. This study demonstrates the potential of CRISPR/Cas9 to develop non-transgenic, gene-edited potatoes with enhanced storage quality, benefiting both growers and the food industry.